Rotavirus y Campylobacter fetus jejuni asociados a un brote de diarrea en terneros - Simhon, Alberto (1984)
Rotaviruses and Campylobacter fetus jejuni are ubiquitous agents of diarrheal disease in animals and humans. Under natural conditions they do not seem to cross inter-species barriers; a zoonosis has not been documented for man. However, animal rotaviruses might contribute to the emergence of new reassortment strains in view of their segmented genome, and thus, produce new antigenic variants. 00 the contrary, Campylobacter fetus jejuni produces a true zoonosis. Man acquires bacilli by ingesting water and foodstuffs contaminated with feces from infected animals. In an outbreak of diarrhea in 22 calves, rotavirus was detected in 8 (36%) and Campylobacter in 6 (27%). Three (14 %) calves experienced double infection. There were no human cases involved in this outbreak.